A09 The Enroll-HD Care Improvement Committee: How Enroll-HD Can Improve Quality of care in HD. (17th September 2014) - Nance, M; Guttman, M
Abstract : Background: Enroll-HD is an international, prospective, longitudinal observational study of Huntington's disease subjects. The objectives of the study include: To improve our understanding of the clinical signs and symptoms and the disease mechanisms of HD To foster good clinical care and improve health outcomes To enhance the design and expedite the conduct of clinical trials Aims: The Care Improvement Committee (CIC) is charged with improving the care of patients with HD so that we can improve outcomes based on prospective data and evaluating best practices as stated in Objective 2. Methods/techniques: The CIC has membership from USA, Canada, Norway, Scotland and New Zealand and includes neurologists, neurogeneticists, nurse specialists, health services researchers and HD family members and advocates. The first CIC project involves a survey of all Enroll-HD sites. It will assess the clinical care models employed by different centres to better understand how HD clinical services are being delivered internationally at expert sites. Initial survey results will be presented. Based on successful quality improvement initiatives in other medical conditions like Cystic Fibrosis, Parkinson's disease and cardiovascular surgery, CIC will assess the effects on HD patient outcomes, initially in symptomatic patients, based on case-mix patient factors, treatment factors and centre effects. As an initial strategy the existing Registry database is being analysed to identify trends and generate hypotheses. Details of the analysis plan will be presented. Conclusions: The primary objective of the CIC is to evaluate cross-sectional and longitudinal data obtained in Enroll-HD in an attempt to determine best practices that are involved in improved outcomes of HD patients. This prospective, data-driven strategy is designed to provide information on how to improve outcomes and provide evidence for future patient care guidelines in HD.